The language of Patriarch Filaret’s sermons (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article deals with the research of structural and grammatical and semantic and syntactic peculiarities of Patriarch Filaret’s sermons. The author investigates the most widespread grammatical constructions and analyzes definite syntactic structures.
Keywords: sermon; construction; linguistic, grammatical and stylistic peculiarities